Benchmarking and Best Practices as Strategies to Improve the Quality of Islamic Education - Rini Asmiati; Siti Julaiha (Journal of Educational Management Research, 2025)
This research aims to analyze the role of benchmarking and best practices in enhancing the quality of Islamic education. The study examines how benchmarking serves as a systematic comparison tool for identifying outstanding practices that can be adapted to the specific context of Islamic educational institutions. Additionally, the article explores how best practices contribute to the innovation of curriculum, teacher competency, quality management, and creative teaching strategies. The study employs a literature review methodology, drawing on scholarly articles, books, and journals to analyze theoretical frameworks and empirical findings on benchmarking and best practices in Islamic education. The findings indicate that integrating benchmarking and best practices through Total Quality Management (TQM) significantly improves curriculum quality, teaching effectiveness, and teacher professionalism, and fosters a culture of continuous quality improvement. The implications of this study suggest that implementing these strategies can make Islamic education more adaptive, innovative, competitive, and rooted in Islamic values. By adopting benchmarking and best practices, Islamic educational institutions can effectively address existing challenges and ensure sustainable improvements in academic outcomes.